Histological quantification of brain tissue inflammatory cell infiltration after focal cerebral infarction: a systematic review. (1st March 2014) - Russek, Natanya S.; Jensen, Matthew B.
<x xml:space="preserve">Abstract</x> Ischemic stroke is a leading cause of death and disability, and current treatments to limit tissue injury and improve recovery are limited. Cerebral infarction is accompanied by intense brain tissue inflammation involving many inflammatory cell types that may cause both negative and positive effects on outcomes. Many potential neuroprotective and neurorestorative treatments may affect, and be affected by, this inflammatory cell infiltration, so that accurate quantification of this tissue response is needed. We performed a systematic review of histological methods to quantify brain tissue inflammatory cell infiltration after cerebral infarction. We found reports of multiple techniques to quantify different inflammatory cell types. We found no direct comparison studies and conclude that more research is needed to optimize the assessment of this important stroke outcome.